ASEAN Moslem Community as Track-9 on Multitrack Diplomacy for The Conflict Resolution in Southeast Asia Region - Effendi, Tonny Dian (Jurnal Hubungan Internasional, 2013)
ASEAN Community 2015 still needs many preparations for its implementation. Southeast Asian peoples should prepare their change of mind to view their regional organization. The epistemic community had significant roles to creating network and work together inside their fields and make spillover effect to public. ASEAN Moslem Community is one of the ideas which can support the community on 2015. This organization is not only establishing a network for cooperation, but also it will contribute for conflict resolution in this region relate with moslem issues. This community will play roles as one of multitrack diplomacy for conflict resolution. As Non Governmental organization, this community will have flexible on its activities and relatively can be accepted by the people. But, it should to consider as a neutral community in some conflict or it will lose its credibility.